Nursing history and slavery history: a parallelism - Mariano Monge Juárez (Universidad de Alicante, 1999)
Traditional historiography often marginates some social classes just as it marginates certain professional sectors, even if they have represented a paramount landmark in the evolution of mankind. Seldom has research ventured into the history of slavery although it has had great importance upon the economy, politics and culture of America, Africa and Europe. This article aims to find a meeting point between Nursing History and Slavery History, both marginalized from social sciences. We attempt to reconstruct here the system for the provision of sanitary care to the enslaved Lima population in the first half of the 18th century, and above all,examine who was responsible for such care. Our hypothesis is that, only nurses either moved by feelings of Christian charity or by the slaves owners' own interests, were the health care providers at the time, as doctors were prevented from helping such a population. In this way, a direct parallelism between a marginalized social class: the slaves, and a profession: nursing, is established.